2007
DOI: 10.1111/j.1460-9568.2007.05742.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of group III metabotropic glutamate receptors results in impairment of LTD but not LTP in the hippocampal CA1 region, and prevents long‐term spatial memory

Abstract: Recently it has emerged that hippocampal long-term depression (LTD) may play an important role in the acquisition and storage of spatial memories. This form of synaptic plasticity is tightly regulated by metabotropic glutamate receptors (mGluRs) that negatively couple to adenylyl cyclase. Activation of group III mGluRs is necessary for persistent hippocampal LTD, but is not required for depotentiation or long-term potentiation (LTP) in the dentate gyrus in vivo. In the CA1 region antagonism of group III mGluRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 50 publications
(108 reference statements)
2
19
1
Order By: Relevance
“…Group II mGluRs are expressed in all regions of the hippocampus (Petralia et al, 1996) and act primarily as presynaptic autoinhibitory receptors that regulate release of glutamate from synaptic terminals that innervate excitatory and inhibitory neurons. Group II mGluR regulation of long-term depression (LTD) in the hippocampus has been shown to play a key role in spatial learning and memory (Altinbilek and Manahan-Vaughan, 2007). Results from our Western blot studies using an antibody that detects both mGluR2 and mGluR3 (mGluR2/3) showed that mGluR2/3 levels were reduced in hippocampus from both 2BC drinking (non-dependent) and CIE/2BC treated (dependent) CCL2-tg mice compared to non-tg mice of the same alcohol treatment group (Gruol et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Group II mGluRs are expressed in all regions of the hippocampus (Petralia et al, 1996) and act primarily as presynaptic autoinhibitory receptors that regulate release of glutamate from synaptic terminals that innervate excitatory and inhibitory neurons. Group II mGluR regulation of long-term depression (LTD) in the hippocampus has been shown to play a key role in spatial learning and memory (Altinbilek and Manahan-Vaughan, 2007). Results from our Western blot studies using an antibody that detects both mGluR2 and mGluR3 (mGluR2/3) showed that mGluR2/3 levels were reduced in hippocampus from both 2BC drinking (non-dependent) and CIE/2BC treated (dependent) CCL2-tg mice compared to non-tg mice of the same alcohol treatment group (Gruol et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, exogenous activation of Group III mGluR receptors has been demonstrated to reduce the probability of epileptiform activity (Ngomba et al 2005). This anticonvulsant activity of Group III mGluR is not likely to be due to long-term synaptic plasticity (Altinbilek and Manahan-Vaughan 2007), however, because mGluR-mediated long-term synaptic plasticity is substantially reduced during epileptogenesis (Kirschstein et al 2007). These findings suggest that the persistence of the chronically epileptic state is likely to involve multiple mechanisms of metaplasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, intracerebral application of the antagonist, CPPG, was found to impair the expression of LTD, but not LTP, in both CA1 and the dentate gyrus [178,204], whilst L-AP4 application inhibits the induction of LTP in these regions [196,204]. Interestingly, L-AP4 was also shown to induce a form of chemical LTD at both of these synapses [205,206], a finding which has since been replicated in the LPP in vitro with the mGlu8 agonist DCPG [207].…”
Section: Hippocampal Plasticitymentioning
confidence: 79%
“…Interestingly, L-AP4 was also shown to induce a form of chemical LTD at both of these synapses [205,206], a finding which has since been replicated in the LPP in vitro with the mGlu8 agonist DCPG [207]. Most importantly, however, this in vivo work revealed an impairment in long-term spatial memory following daily treatment with CPPG, indicating a direct link between group III mGlu receptors and hippocampusdependent memory function [178]. In line with this, mGlu4, mGlu7 and mGlu8 KO mice have all been found to exhibit impairments in learning and memory tasks associated with hippocampal function [208][209][210][211], but see [212].…”
Section: Hippocampal Plasticitymentioning
confidence: 87%
See 1 more Smart Citation